Validación del Inventario de Calidad de las Relaciones en una Muestra Peruana de Adolescentes y Asociaciones con Apego de Pares - Yearwood, Karen; Vliegen, Nicole; Luyten, Patrick; Chau, Cecilia; Corveleyn, Jozef (Psykhe, 2018)
Research concerning adolescent peer relations and peer attachment is scarce, and more so in Spanish-speaking populations. The aims of this study were twofold: (a) to adapt the Quality of Relationships Inventory (QRI) to Spanish and (b) to assess its psychometric properties in the context of peer relations in a sample of N = 269 Peruvian adolescents. Internal consistency was adequate. The factor structure of the instrument was assessed by means of confirmatory factor analysis (CFA) and multidimensional scaling (MDS). Convergent validity was explored by analyzing the associations between the QRI subscales and the peer subscales of the Inventory of Parent and Peer Attachment (correlations ranged from r = .37 to r = .61) and discriminant validity by exploring the associations between the QRI subscales and both internalizing and externalizing symptoms (correlations ranged from r = .27 to r = .35). Results showed that the QRI on its Spanish version is a reliable tool for the assessment of the quality of peer relationships within a Peruvian context when taking some considerations into account regarding the conflict scale.